Implementation of Prototype Method in School Payment Information System of SMP AL- Mushlis Karawang - Muhamad Tabrani; suhardi Suhardi (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2022)
The development of technology in the field of information systems is currently experiencing a very rapid development, with the presence of an information system, many things can be done easier and faster. For the implementation of tuition payments at Al-Mushlih Junior High School, a web-based information system is needed, which is used for the process of SPP payment services. Currently, the management of school fees payments is still done in the traditional way by entering them in the general ledger, which is very time consuming, especially in the days of school fees payments. Errors often occur when recalling data, and it takes a long time because of the need to check the payment archive in the general ledger. By using a web-based information system, retrieving payment data when needed becomes easier and very fast. The prototype method is used as a reference for system design and development, and it is expected that the new system will facilitate the work of staff and the information produced will be more accurate and precise when reports are generated. Supporting software such as web server, PHp, and Mysql is needed to create a website. The results of the information system created can later process student data, payment data, and transaction data for report generation over a period of time.